Penguatan Kerja Sama Lintas Negara dalam Penegakan Hukum Perdagangan Satwa Liar - Rizki Zakariya (Jurnal Hukum Lex Generalis, 2021)
Indonesia is a country with the highest animal wealth in the world. However, the wealth of these animals is threatened by the wildlife trade. Therefore, law enforcement for wildlife trade is carried out. However, the perpetrators develop their modus operandi to deceive law enforcers, one of which is through cross-state jurisdictions. The results of this study indicate that the urgency of strengthening cross-border cooperation in eradicating wildlife trade is due to the high potential for biodiversity in Indonesia, accompanied by high cases of animal trafficking, law enforcement that has not been optimal, and problems in regional and international cooperation in eradicating wildlife trade. illegally wild. Then efforts that can be made to strengthen this cooperation are by improving the provisions in CITES, improving the governance of CITES authorities in Indonesia and strengthening cooperation between countries in the ASEAN region.